2020
DOI: 10.3390/nu12092702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sweet-Liking on Body Composition Depend on Age and Lifestyle: A Challenge to the Simple Sweet-Liking—Obesity Hypothesis

Abstract: Taste hedonics drive food choices, and food choices affect weight maintenance. Despite this, the idea that hyper-palatability of sweet foods is linked to obesity development has been controversial for decades. Here, we investigate whether interpersonal differences in sweet-liking are related to body composition. Healthy adults aged 18–34 years from the UK (n = 148) and the US (n = 126) completed laboratory-based sensory tests (sucrose taste tests) and anthropometric measures (body mass index; BMI, body fat; fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 88 publications
3
35
1
Order By: Relevance
“…Previous studies have reported an association between sensitivity to reward and some unhealthier behaviours, such as higher fat intake, higher alcohol consumption, smoking frequency, while only a trend was observed with sugar intake [ 93 , 102 ]. Furthermore, no difference between the clusters was found in BMI, in line with some studies [ 32 ] even if the results in the literature are mixed [ 88 ]. Nevertheless, the current findings require further investigation to understand more deeply the role of these and other personality traits in food preferences and consumption behaviours, specifically in relation to sweet foods taking into account gender differences.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies have reported an association between sensitivity to reward and some unhealthier behaviours, such as higher fat intake, higher alcohol consumption, smoking frequency, while only a trend was observed with sugar intake [ 93 , 102 ]. Furthermore, no difference between the clusters was found in BMI, in line with some studies [ 32 ] even if the results in the literature are mixed [ 88 ]. Nevertheless, the current findings require further investigation to understand more deeply the role of these and other personality traits in food preferences and consumption behaviours, specifically in relation to sweet foods taking into account gender differences.…”
Section: Discussionsupporting
confidence: 86%
“…In keeping with most of the literature we identified three clusters [ 86 ]. However, compared to studies that classified sweet likers based on their response to sucrose aqueous solutions [ 20 , 32 , 88 ], we did not identify distinct Sweet Dislikers. Instead, in line with Kim et al [ 18 ], we found Moderate Sweet Likers whose sweetness/liking slopes were less steep than those of the High Sweet Likers.…”
Section: Discussioncontrasting
confidence: 78%
“…individuals expressing aversive responses to high sweetness; SDs). In a multi-country study, we recently found that SLs had either lower fat mass or greater fat free mass than SDs (Iatridi, Armitage, et al, 2020). We concluded that, for SLs, hedonic response to sweetness matched their bodily needs, either in respect to energy stores or energy requirements.…”
Section: Introductionmentioning
confidence: 81%
“…Conversely, human body primarily defends undersupply in order to prevent or reverse body mass loss (Speakman et al, 2011). Further, SLs also exhibited behavioural characteristics analogous to those of high interoceptive performers, such as enhanced trait-hunger, intensity seeking, and reward sensitivity (Iatridi, Armitage, et al, 2020). Collectively then, interoception appears to be a good candidate to explain the observed effects of sweet taste phenotype on body composition and psychometric profiles.…”
Section: Introductionmentioning
confidence: 97%
“…A few studies examined the relationship between the sweet-liking phenotype and body mass index (BMI), with mixed results. While Garneau et al [32] did not find any association in a sample of children and young adults, Iatridi et al [33] reported that sweet likers had an higher BMI and fat-free mass but only in the older groups. Based on these findings, the authors suggest that exposure to an obesogenic environment contributes to an increase in sweet-liking.…”
Section: Obesity and Food Preferencesmentioning
confidence: 88%